Analisa porositas alumunium alloy terhadap variasi temperatur pada proses squeeze casting semi solid - Asroni Asroni; Tri Cahyo Wahyudi; Adek Tri Setiawan (Universitas Muhammadiyah Metro, 2023)
Direct squeeze casting is a process in which molten metal is cooled by applying pressure directly which aims to prevent gas porosity and shrinkage in a material. This process has the advantage of minimizing the occurrence of gas porosity and shrinkage, so there is no material disposal. The purpose of this study to determine the results of good porosity in aluminum Alloy materials with squeeze casting process. The research method is experimental by designing and making test samples of laboratory scale casting squeeze casting. The test was conducted with a variation of 300oC, 400oC, and 500oC pressure of 176 MPa, long pressing 75 seconds, holding time 9 minutes, the specimen was then tested to determine how the influence of mold temperature variations on the results of porosity and density. From the results of the study it can be concluded that the porosity defects of the casting are influenced by the given temperature variation and constant pressing. Many air cavities are trapped in the object product, the more porosity defects that will affect the resistance of the specimen, because the more the object product is solid or reduced porosity defects, the resistance of the specimen will increase. The smallest or good porosity value is shown by specimens with a temperature variation of 5000C which is 17.96%.